Transformasi Digital Dalam Pengembangan Manajemen Pelatihan untuk Meningkatkan Kompetensi TIK Guru SD Negeri 58 Kota Banda Aceh - Mauladiah, Mauladiah; Syarfuni, Syarfuni; Novita , Rita (Cetta: Jurnal Ilmu Pendidikan, 2024)
Globally, digital transformation has become a primary driver in reshaping the education paradigm, including in the development of training management to enhance ICT competencies among elementary school teachers. This study aims to explore the development of management and the impact of digital transformation management training on enhancing ICT competencies among teachers at SD Negeri 58 in Banda Aceh. The study adopts a Research and Development research design, focusing on developing a digital transformation-based management model to improve ICT competencies. Subjects included all 9 teachers from SD Negeri 58 in Banda Aceh and 2 Management and IT experts. The research procedure utilizes the ADDIE development model. Data was collected through questionnaires, interviews, observations, and tests, which were then analyzed descriptively and analytically. The results indicate that implementing a digital transformation-based training management model successfully enhances ICT competencies among teachers through an online approach using the Google Classroom platform. This approach allows teachers to access the latest educational resources, participate in remote training, and share best ICT practices via digital platforms. Teachers can continually update their knowledge, share best practices, and effectively implement innovations in ICT education at schools. This supports not only the improvement of teaching quality but also strengthens teachers' competencies in developing skills relevant to current needs. The integration of technology can enhance teachers' readiness to face current technological advancements. Therefore, it can be concluded that digital transformation in training management development can enhance ICT competencies among teachers at SD Negeri 58 in Banda Aceh.